Genetic diversity of the table beet (Beta L.) collection at VIR as a potential source for breeding (a review) - D. V. Sokolova (Труды по прикладной ботанике, генетике и селекции)
This review presents brief information about the history of the table beet (Beta vulgaris L. subsp. vulgaris var. conditiva Alef.) collection at the N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR), its composition, research trends, and significance for domestic breeding. The collection started in 1924 with Vavilov’s collecting activities. Currently, the collection consists of 2512 accessions; the table beet variety is represented by 461 accessions from 45 countries, collected in numerous expeditions, obtained from foreign genebanks through germplasm exchange and seed requests, received from domestic and foreign breeders, plus materials developed by VIR researchers. Table beet is an economically important, high-yielding, ubiquitous crop that has a wide cultivation area and is a valuable biochemical food product with beneficial effects on human health.The information is provided on the genetic diversity of VIR’s table beet collection, including current trends of its study and use in breeding. Characteristics of table beet accessions available in the collection, their morphological features and value, and the names of accessions from different trait groups and genetic sources are described. Presently, 125 cultivars and 38 F1 hybrids of table beet are listed in the State Register of Breeding Achievements of the Russian Federation, 70% of which are products of domestic breeding.